Genetic analysis of four indigenous duck populations of north-east India using microsatellite markers - DAS, BULA; DAS, ARPANA; PHOOKAN, ARUNDHATI; ZAMAN, G; AZIZ, A; DAS, P J; BHARALI, K (The Indian Journal of Animal Sciences, 2019)
The genetic diversity and phylogenetic relationship of four duck populations, viz. Pati, Nageswari, Manipur and Tripura ducks of north eastern region of India were investigated by employing genetic polymorphisms of 25 microsatellites. The mean observed and effective number of alleles were found to be 2.670 and 1.949 respectively in all the four duck populations over 25 loci. The mean expected heterozygosity (He) was lower than the mean observed heterozygosity (Ho). Among all the populations, the He of Manipur ducks was the highest (0.443), followed by Tripura ducks (0.435), whereas Pati ducks was the lowest (0.396). The average He of all populations for all the loci was 0.420. The average PIC of all sites and populations was 0.366. However, CAUD007 in Manipur, Nageswari and Pati ducks, CAUD009 in Pati ducks, CAUD069 in Tripura ducks, and CAUD012 in all the four duck populations were found to be monomorphic. The test of Hardy- Weinberg Equilibrium showed that most of the loci in all the four populations were in Hardy-Weinberg disequilibrium. The FST value ranged between 0.000(CAUD012) and 0.512 (CAUD009) for each locus individually. The mean FST was 0.120. The genetic distance between Tripura ducks and Manipur ducks was the longest (0.2495) followed by Manipur and Nageswari ducks (0.2090) and, Nageswari and Pati ducks (0.1790).